Event‐based privacy‐preserving security consensus of multi‐agent systems with encryption–decryption mechanism - Liu, Jinliang; Deng, Ying; Zha, Lijuan; Xie, Xiangpeng; Tian, Engang (International journal of robust and nonlinear control, 2024)
The article concentrates on exploring the issue of privacy‐preserving sliding mode consensus of multi‐agent systems (MASs) with disturbance. An encryption and decryption algorithm has been proposed to address data security and privacy issues during data transmission. To optimize network resource allocation, a dynamic event‐triggering mechanism has been introduced, which reduces the number of encrypted data while saving the computation cost. The consensus performance based on the sliding mode control strategy is achieved when the reachability of the slide‐mode surface is guaranteed, and then the slide‐mode controller is developed. Finally, an empirical demonstration through a numerical example validates the efficacy of the proposed strategy.